Focal segmental glomerulosclerosis: current status of the problem - I. T. Murkamilov; I. S. Sabirov; V. V. Fomin; Zh. A. Murkamilova (Архивъ внутренней медицины, 2020)
One of the most prognostically unfavorable variants of glomerulopathy is focal segmental glomerulosclerosis (FSHC), which is detected by nephrobiopsy in 5-20% of patients with nephrotic syndrome (NS) and in 15% of adult patients with chronic glomerulonephritis. FSGS recurs in a transplanted kidney in 30-50% of patients. Among adult patients with FSH, men predominate. A poor prognosis of FSHC is explained by the heterogeneity of the disease and is exacerbated by a poor response to treatment. According to current data, FSGS is characterized by sclerosis of the mesangial matrix, hyalinosis, damage to capillaries, an increase in foam cells and their adhesion between the glomerular bundle and the Bowman capsule. In 2004, the following histological variants of FSGS were proposed: apical, perichillary, collaborating, cellular and classical. Each histological variant of FSGS differs in etiology, response to treatment, and prognosis. The clinical diagnosis of primary FSHC should be based on the exclusion of secondary causes of the disease. Focal sclerotic changes in the glomeruli can be caused by various factors and occur in various conditions, including the existing kidney pathology. According to international recommendations for the treatment of FSHS, one should focus on the amount of daily proteinuria. For patients with FSHS without pronounced proteinuria, the use of angiotensin converting enzyme inhibitors (ACE inhibitors) or angiotensin II receptor blockers (ARBs) is recommended. In FSGS and NS, immunosuppressive therapy is used along with ACE inhibitors or ARB II. For adult patients, glucocorticoids (HA) are prescribed daily in a single dose at a dose of 1 mg / kg per day, the maximum dose is 80 mg with a daily intake and 120 mg with an alternating regimen. Resistance to HA is detected in the absence of effect after 16 weeks. In the presence of contraindications or intolerance to HA, calcineurin inhibitors are used. The recommended initial dose of cyclosporine is 2 mg / kg / day, taken twice a day with a gradual increase to 3.5-4 mg / kg / day. The duration of therapy with satisfactory tolerance to cyclosporine is more than six months. After achieving complete remission, the dose of cyclosporin is gradually reduced by 0.5 mg / kg / day to the minimum effective dose (1.5-2 mg / kg / day) and such maintenance therapy is carried out for 1-2 years. A treatment option is possible using lower doses of HA and cyclosporine, or a combination of mycophenolate mofetil with a high dose of dexamethasone.